Effects of Different Harvest Stages on Yield and Essential Oil Content of Thyme (Thymus kotschyanus Boiss. & Hohen) - Kizil, Suleyman (Asian Journal of Chemistry, 2010)
Effects of harvest at the beginning of flowering, full flowering and after full flowering on yield and essential oil of Thymus kotschyanus were evaluated under Diyarbakir ecological conditions during 2002-03 and 2003-04 growing seasons. Harvest times had significant effect on plant height, fresh and dry herbage, dry leaf yield, essential oil and yield. Maximum thymol (48.9%) was obtained when the harvesting was done at the beginning of flowering.